Transforming global governance: Crafting sustainable peace through Global South perspectives - Ibrahim Khan (Intergenerational Justice Review)
This essay examines the need for long-term peacekeeping to protect future generations, drawing on early twentieth-century critiques of international legal and political infrastructure, from parts of the world now commonly referred to as the Global South. It highlights foundational flaws in international organisations and legal structures that perpetuate global inequalities and conflicts. Arguing that sustainable peace requires addressing such structural inequalities and power imbalances, this essay proposes comprehensive reforms to the UN Security Council so as to encourage more representative decision-making. It also emphasises the importance of grassroots movements and disarmament efforts in achieving lasting peace. By bridging historical critiques with contemporary challenges, this analysis offers a framework for transforming global governance to create a more peaceful world for future generations.